Digital Learning Culture in The Pandemic Period for Adults at The Community Learning Center (CLC) in Bandung - Wahyudin, Uyu; Purnomo, Purnomo; Sulistiono, Eko; Najmudin, Muhammad Faisal; Putra, Apriza Hongko (Lembaran Ilmu Kependidikan, 2023)
Community Learning Center (CLC) as a community education unit, has a participatory local approach to program requirements and implementation. During the Covid pandemic, all educational learning unit activities in Bandung were directed by the use of distance learning channels, using the internet as a learning channel. However, the pandemic is a global problem with a fluctuating and urgent number of developments, so the readiness of the education unit is a problem, because the majority of the population studying CLC are adults without school age. This study uses a quantitative descriptive approach with survey methods to 43 CLC institutions in the city of Bandung with 228 respondents as research residents. The results of the study show that CLC has facilitated learning residents to discuss by providing zoom meeting services, google meet and utilizing Whatsapp as a learning channel. Digital-based adult learning education has been implemented in CLC throughout the city of Bandung in the learning system, although there are still some CLC that are needed along with readiness for digitization. The inhibiting factor is for residents who study the category of adult digital immigrants, they still need to be assisted by the closest people to operate digital devices.